Activity and selectivity enhancement of silica supported cobalt catalyst for alcohols production from syngas via Fischer-Tropsch synthesis. (22nd January 2022) - Du, Hong; Jiang, Miao; Zhao, Min; Ma, Xiuyun; Xu, Zhanwei; Zhao, Ziang
Abstract: Synthesis of mixed alcohols together with clean fuels from syngas via Fischer-Tropsch synthesis is an attractive route for the utilization of coal, natural gas and biomass. In this work, a monometallic cobalt catalyst (Co/SiO2 -EOAM) was synthesized by impregnation using ethanolamine modified silica pellet as support and employed for the conversion of syngas. The combustion of carbon and nitrogen species during the calcination of catalyst facilitated the interaction between cobalt and support, which promoted the cobalt dispersion while inhibited the reduction of cobalt oxide. The Co/SiO2 -EOAM catalyst exhibited much higher activity and selectivity to alcohols compared to un-modified silica supported cobalt catalyst (Co/SiO2 ). The higher activity was resulted from the improved cobalt dispersion. The co-existence of abundant metallic cobalt and Co 2+ species were responsible for the increasing of alcohols selectivity. Highlights: Efficient Co/SiO2 was developed for mixed alcohols synthesis from syngas. Higher Co dispersion is obtained by using ethanolamine modified silica as support. Higher amount of Co 0 active sites leads to increased activity. Co-existence of Co 0 and Co 2+ is responsible for the alcohols formation.